Design, synthesis and biological evaluation of novel benzocoumarin derivatives as potent inhibitors of MAO-B activity - Meletli, Furkan; Gunduz, Cihan; Alparslan, Mustafa Muhlis; Attar, Azade; Demir, Serap; Iskit, Ece; Danis, Ozkan (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
The continued research of novel reversible inhibitors targeting monoamine oxidase (MAO) B remains crucial for effectively symptomatic treatment of Parkinson's disease. In this study we synthesized and evaluated a new series of 3-aryl benzo[g] and benzo[h] coumarin derivatives as MAO-B inhibitors. Compound A6 has been found to display the most potent inhibitory activity and selectivity against the MAO-B isoform (IC50 = 13 nM and SI = >7693.31 respectively). Inhibition mode of A6 on MAO-B was predicted as mixed reversible inhibition with a Ki value of 3.274 nM. Furthermore, in order to elaborate structure-activity relationships, the binding mode of A6 was investigated by molecular docking simulations.
Keywords: Benzo[g]coumarin; Benzo[h]coumarin; Monoamine oxidase; Parkinson's Disease; Molecular docking; 3-PHENYLCOUMARINS; 3-ARYLCOUMARINS; COUMARINS; DOCKING; SERIES; Pharmacology & Pharmacy; Chemistry